A Review of Low-Level Laser Therapy for Spinal Cord Injury: Challenges And Safety - Vafaei-Nezhad, Saeed; Pour Hassan, Mahnaz; Noroozian, Mohsen; Aliaghaei, Abbas; Shirazi Tehrani, Atefe; Abbaszadeh, Hojjat-allah; Khoshsirat, Shahrokh (Journal of Lasers in Medical Sciences, 2020)
Introduction: Damage to the spinal cord is a central nervous system disorder that results in direct damage to neural cells (axons, cell bodies) and glia, followed by autonomic, motor and sensory impairments. Inflammatory response after this injury can contribute to secondary tissue damage that leads to further behavioral and functional disorders. Inflammation is a complex process, which occurs after an injury. If this progressive process is not well controlled can lead to additional damage to the spinal cord which is preventing neural improvement and regeneration and, which ultimately will not provide good clinical consequences. Inflammation in the injured spinal cord is a physiological response that causes the death of glial and neuronal cells. The reduction of the initial inflammatory process after damage to the spinal cord is one of the important therapeutic strategies. It has been proposed that low-level laser (LLL) therapy, as a noninvasive manner, can modulate inflammatory processes, which leads to a significant improvement in neurological symptoms after spinal cord injury (SCI). Methods: A comprehensive review was performed on SCI, the etiologies, and treatment methods using the keywords spinal cord injury, low-level laser, and inflammation in valid medical databases such as Google Scholar, PubMed, and Elsevier (76 articles). Among the collected papers, articles that were most relevant to the purposes of the study were selected and studied. Results: LLL therapy was able to reduce inflammation and also attenuate neuronal damage after spinal cord damage. Conclusion: In conclusion, the present study illustrates that LLL therapy has positive effects on improving functional recovery and regulating the inflammatory function in the SCI.